PHYSICO-CHEMICAL PROPERTIES OF INHIBITORS BASED ON SODIUM-CARBOXYMETHYL CELLULOSE AND PHOSPHORUS COMPOUNDS (Scientific journal of the Fergana State University, 2026)
As a result of industrial corrosion, metal materials lose their natural state over time and cause environmental pollution. As a result of adsorptive interaction with metal, how its protective properties are manifested at different temperatures and the study of reaction mechanisms, production of new effective inhibitors is one of the urgent tasks today. Iron-based alloys, which are the main materials of modern techniques and technologies, undergo corrosion under the influence of moisture, air oxygen, nitrogen, sulfur oxides and other chemically active substances. Since the independence of our republic, extensive measures have been taken to develop new types of products in the chemical industry, to organize scientific research’s at a high level and to supply the local market with chemical reagents that can replace imports and certain results have achieved in solving of these problem. It consists in elaboration inhibitors based on sodium-carboxymethylcellulose and phosphorus-containing compounds, which effectively protect metals from corrosion, and determining the physico-chemical properties of their effects. Electrochemical, gravimetric, IR-spectroscopic and X-ray phase analysis methods were used in this article. Phosphorous derivatives of sodium carboxymethylcellulose, diethylamine and aniline were used as inhibitors for the first time. The mechanism of their action to protect metals during corrosion is proposed. The level of protection, braking coefficient and optimal conditions of use of high-performance inhibitors at different concentrations have been determined. The theoretical significance of the obtained results is that the synthesized sodium-carboxymethylcellulose and phosphorus-containing inhibitors were used as two-component systems.